Learning Media Visualisation of Distance in Augmented Reality-Based Three-Dimensional Space - Baeha, Nadilah Hasfahani; Zahnur; Oktavia, Rini (Journal of Education Reseach and Evaluation, 2025)
One of the challenges encountered by students when studying distance in space is the difficulty in conceptualizing abstract mathematical concepts, such as determining perpendicular line segments in a cube represented in a two dimensional image. The visualization of abstract mathematical objects can be represented using augmented reality (AR) technology. This technology turns images of objects into virtual ones that appear in the real world. Previous studies showed that there is a need to enrich AR application with more multimedia content. Developing an AR system utilizing smartphones has become a prevalent endeavor recently. This study aims to develop augmented reality-based learning media to enhance students' comprehension of the concept of distance in three-dimensional space. This study employed a research and development (R&D) approach utilizing the ADDIE model, comprising five stages: analysis, design, development, implementation, and evaluation. The sample consisted of 36 students in the  12th-grade from a high school located in Indonesia, and the experiment employed a pretest-posttest control group design. The Mann-Whitney U test showed no statistically significant difference between the pretest scores of the experimental and control groups. However, the posttest results showed the experimental group had a higher mean rank score (22.36) than the control group (14.64), with a p-value of 0.017 and effect size of 0.42. This indicates that the learning media has a meaningful impact, which can significantly improve students' ability to understand the material on distance in a three-dimensional space.